Exploring the Effectiveness of Different Learning Methods: A Comparative Analysis - Mai Idrees Zaghab (2025)
This theoretical paper scrutinises the evolution of language teaching methods across the twentieth and twenty-first centuries, emphasising the continuous effort to enhance learning environments and outcomes. It investigates the Total-Physical Response (TPR), The Eclectic Approach, Task-Based Language Teaching (TBLT), and Suggestopedia. through a comparative analysis, the study aims to identify effective strategies for different learners, considering their styles and subject areas, each method is scrutinized based on its principles, techniques, strengths, and weaknesses, highlighting the need for adaptable methodologies that promote engagement and meaningful language acquisition. The findings and discussion offer insights into effective teaching methods, emphasizing personalized approaches to improve learning outcomes.